Evaluating pedagogical competence of pre-service teachers in Islamic education: Insights from School Field Practice program - Wahdah, Wahdah; Elfri, Rini (UIN Raden Mas Said Surakarta, 2024)
Teacher competence is a key determinant of educational quality, particularly in the field of Islamic education where both pedagogical skills and religious teachings must be integrated. This study aims to evaluate the pedagogical competence of pre-service teachers from the Islamic Education Program at Universitas Muhammadiyah Pontianak during their School Field Practice (PLP). Using a mixed-methods approach, the research assesses pre-service teachers' abilities in designing, implementing, and evaluating lesson plans. Quantitative data were collected through questionnaires, while qualitative data were derived from lesson plans and reflective documentation. The findings reveal that pre-service teachers demonstrated strong competence in lesson planning and implementation, with average scores placing them in the